(untitled) - Lang, Chris (Uruguay, 2002)
The report was written to encourage debate on the issues raised about the pulp and paper industry and the development of industrial plantations in the Mekong region. The aim of the report is not to provide "solutions" or recommendation, but to support the rights of communities to make their own decisions over the management of their rivers, farmlands and forests.
Keywords: Pulp,Paper,Bột giấy,Giấy; Technology,Công nghệ